PENGARUH MOTIVASI INTRINSIK DAN KOMUNIKASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. SELARAS BINTANG SEJAHTERA KOTA DEPOK - Sarah Wiwanda; Lilis Suryani (Yayasan Education and Social Center, 2026)
The purpose of this study is to determine the influence of intrinsic motivation and work communication on employee performance at PT. Aligned with the Prosperous Star of the City of Depok. The method used is quantitative. The sampling technique uses saturated sampling where all members of the population are used as samples, thus the sample in this study is 58 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The population in this study is employees of PT. In line with the Prosperous Star of Depok City and the number of saturated samples amounted to 58 respondents. The method of data collection is through questionnaires with a likert scale, observation, and literature study. The results of this study are that intrinsic motivation has a significant effect on employee performance with a determinationcoefficient of 84.4% and the hypothesis test was obtained by calculating > ttable or (17,407 > 1,672). Work communication had a significant effect on employee performance with a determination coefficient of 85.2% and the hypothesis test was obtained by calculating > ttable or (17,976 > 1,672). Intrinsic motivation and work communication simultaneously had a significant effect on employee performance with the regression equation Y = 0.045 + 0.497X1 + 0.483X2, nii coefficient of determination was 90.3% while the remaining 9.7% was influenced by other factors. The hypothesis test obtained the value of Fcal > Ftabel or (254.722 > 3.16).